PENGARUH WARNA MERAH DAN TEKSTUR TERHADAP PERSEPSI TERMAL SECARA ADAPTIF - Angeline Hardiyani, Vania; Enggar Sari , Wulani (Jurnal Riset Arsitektur, 2025)
Abstract - Buildings are designed to accommodate activities and protect users from the surrounding environment climate. Thermal comfort is adaptively influenced by physical conditions and human thermal perception. Adaptivity is defined as the capacity or ability of the building to maintain its comfort by responding to changes. Adaptivity is not only seen from the physical conditions alone, but also from the thermal perception associated with human physiology and psychology. Thermal perception can be explored through changes in color and texture accordingly. The purpose of this research is to find out the most effective red color and material texture for the design of learning spaces, so that it can be applied to other architectural designs. The research used an experimental method with a quantitative approach through a Virtual Reality test model. The test model is in the form of a Parahyangan Catholic University Architecture studio room that is adaptively developed in the fields of walls, floors, and ceilings based on color and texture theory. Data collection of thermal perception in the form of thermal judgment and thermal sensation is done using a questionnaire validated by a sweat content test kit. The data were then processed using the ANOVA statistical method to determine the correlation relationship that occurs based on the theory of thermal perception. This study shows that thermal perception is formed by thermal sensation and thermal judgment. Both have a strong relationship with an inverse linear direction. Virtual Reality simulation with a red color model supported by wood texture is stated to have the most influence on the thermal perception of respondents. Keywords: thermal perception, penliatai, thermal judgment, studio space